PERFORMANCE OF MERGER AND ACQUISITION, DIRECTOR EXPERIENCE, AND MODERATION EFFECTS OF BOARD CHARACTERISTICS, BIDDER CHARACTERISTICS, AND TYPE OF MERGER AND ACQUISITION - Shindy Dwita Nuansari (Manajemen Bisnis, 2020)
This research focuses on influence of the experience of independent directors (two tier systems) on mergers acquisitions performance and considers several other factors as moderation. Purpose of this study was to determine the effect of the experience of independent directors to be moderated by board characteristics, bidder characteristics, and types of merger acquisitions on merger and acquisition performance and to be controlled by independent director’s age. Research obtained from the company's financial and annual report data in 2009 - 2019. The dependent variable used in this study was merger and acquisition performance. Independent variable used in this study is independent director experience. Moderating variables in this are board characteristics, bidder characteristics, mergers and acquisitions types. The results of this study proves that the experience of director experience positively influences performance of merger and acquisition, board and bidder characteristics, type of merger and acquisition strengthen the positive influence of the experience of independent directors on merger and acquisition performance.